AL-HAKIM AL-TIRMIDHI’S VIEWS ON TAFSIR AND TA’WIL (The Journal of Interdisciplinary Human Studies, 2026)
This article examines al-Hakim al-Tirmidhi’s views on tafsir (exegesis)and ta’wil (interpretation) as reflected in his work “Tahsil nazair al-Qur’an.” It showsthat al-Tirmidhi consistently distinguishes between tafsir an explanation supported bya decisive proof such as a Qur’anic verse and ta’wil, the selection of the most fitting ofa word’s possible meanings. Through an analysis of the five “aspects” (wujuh) that alTirmidhi assigns to the word ta’wil, and a comparison with the usage of Imam al-Maturidiin “Ta’wilat ahl al-sunna,” the article argues that, for al-Tirmidhi, the “aspects” of aQur’anic word are directly bound up with the process of ta’wil, and that “Tahsil nazair alQur’an” constitutes, in effect, an exposition of the methodology of ta’wil and a refutationof those who reject the interpretation of the Qur’an’s ambiguous (mutashabih) verses.
Keywords: al-Hakim al-Tirmidhi, al-Maturidi, tafsir, ta’wil, wujuh wa nazair, Tahsil nazair al-Qur’an, mutashabih, Qur’anic exegesis, diraya.